THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK MOTIVATION AND COMPENSATION ON EMPLOYEE PERFORMANCE AT THE SOUTHEAST ACEH RELIGION MINISTRY - Humayroh Putri Selian; Em Yusuf Iis; Nur Faliza; Ibrahim Qamarius (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to find out about the effect of Transformational Leadership Style, Work Motivation and Compensation on Employee Performance at the Ministry of Religion of Southeast Aceh. The data used in this study are primary data obtained by distributing questionnaires to 54 employees. The technique consists of data instrument test, classical assumption test and hypothesis testing using the help of SPSS software program. The results showed that Transformational Leadership Style had a positive and significant effect on Employee Performance on Employees at the Ministry of Religion of Southeast Aceh. Work Motivation on Employee Performance in Employees at the Ministry of Religion of Southeast Aceh. Compensation on employee performance in employees at the Ministry of Religious Affairs of Southeast Aceh. These findings provide useful for the government to establish strategies related to human resources to improve employee performance.